Effects of exercise training on airway responsiveness and airway cells in healthy subjects - Scichilone, Nicola; Morici, Giuseppe; Zangla, Daniele; Chimenti, Laura; Davì, Eva; Reitano, Simona; Paternò, Alessandra; Santagata, Roberta; Togias, Alkis; Bellia, Vincenzo; Bonsignore, Maria Rosaria (Journal of applied physiology (1985), 2010)
Airway responsiveness to methacholine (Mch) in the absence of deep inspirations (DIs) is lower in athletes compared with sedentary individuals. In this prospective study, we tested the hypothesis that a training exercise program reduces the bronchoconstrictive effect of Mch. Ten healthy sedentary subjects (M/F: 3/7; mean ± SD age: 22 ± 3 yr) entered a 10-wk indoor rowing exercise program on rowing ergometer and underwent Mch bronchoprovocation in the absence of DIs at baseline, at weeks 5 and 10, as well as 4–6 wk after the training program was completed. Exercise-induced changes on airway cells and markers of airway inflammation were also assessed by sputum induction and venous blood samples. Mean power output during the 1,000 m test was 169 ± 49 W/stroke at baseline, 174 ± 49 W/stroke at 5 wk, and 200 ± 60 W/stroke at 10 wk of training ( P < 0.05). The median Mch dose used at baseline was 50 mg/ml (range 25–75 mg/ml) and remained constant per study design. At the pretraining evaluation, the percent reduction in the primary outcome, the inspiratory vital capacity (IVC) after inhalation of Mch in the absence of DIs was 31 ± 13%; at week 5, the Mch-induced reduction in IVC was 22 ± 19%, P = 0.01, and it further decreased to 15 ± 11% at week 10 ( P = 0.0008). The percent fall in IVC 4–6 wk after the end of training was 15 ± 11% ( P = 0.87 vs. end of training). Changes in airway cells were not associated with changes in airway responsiveness. Our data show that a course of exercise training can attenuate airway responsiveness against Mch inhaled in the absence of DIs in healthy subjects and suggest that a sedentary lifestyle may favor development of airways hyperresponsiveness.